Clinical flow cytometric screening of SAP and XIAP expression accurately identifies patients with SH2D1A and XIAP/BIRC4 mutations. Issue 4 (19th February 2014) - Gifford, Carrie E.; Weingartner, Elizabeth; Villanueva, Joyce; Johnson, Judith; Zhang, Kejian; Filipovich, Alexandra H.; Bleesing, Jack J.; Marsh, Rebecca A.
<x xml:space="preserve">Abstract</x> Introduction: X‐linked lymphoproliferative disease is caused by mutations in two genes, SH2D1A and XIAP/BIRC4. Flow cytometric methods have been developed to detect the gene products, SAP and XIAP. However, there is no literature describing the accuracy of flow cytometric screening performed in a clinical lab setting. Methods: We reviewed the clinical flow cytometric testing results for 656 SAP and 586 XIAP samples tested during a 3‐year period. Genetic testing was clinically performed as directed by the managing physician in 137 SAP (21%) and 115 XIAP (20%) samples. We included these samples for analyses of flow cytometric test accuracy. Results: SH2D1A mutations were detected in 15/137 samples. SAP expression was low in 13/15 (sensitivity 87%, CI 61–97%). Of the 122 samples with normal sequencing, SAP was normal in 109 (specificity 89%, CI 82–94%). The positive predictive values (PPVs) and the negative predictive values (NPVs) were 50% and 98%, respectively. XIAP/BIRC4 mutations were detected in 19/115 samples. XIAP expression was low in 18/19 (sensitivity 95%, CI 73–100%). Of the 96 samples with normal sequencing, 59 had normal XIAP expression (specificity 61%, CI 51–71%). The PPVs and NPVs were 33% and 98%, respectively. Receiver‐operating characteristic analysis was able to improve the specificity to 75%. Conclusion: Clinical flow cytometric screening tests for SAP and XIAP deficiencies offer good sensitivity and specificity for detecting genetic mutations, and are characterized by high NPVs. We recommend these tests for patients suspected of having X‐linked lymphoproliferative disease type 1 (XLP1) or XLP2. © 2014 International Clinical Cytometry Society